Anno Dracula, 1959 : Dracula cha cha cha - Newman, Kim (Newman, Kim. Anno Dracula, 2018)
Count Dracula is about to marry the Moldavian Princess Asa Vajda-- his sixth wife. Journalist Kate Reed flies into the city to visit the ailing Charles Beauregard and his vampire companion Geneviève. Finding herself caught up in the mystery of the Crimson Executioner who is bloodily dispatching vampire elders in the city, Kate discovers that she isn't the only one on his trail.